EDUCATION TODAY AND TOMORROW (American Journal of Technology and Applied Sciences, 2023)
This article looks at how we taught yesterday and how we teach today. She emphasizes the need to transform the modern education system to meet the changing demands and needs of children. This statement emphasizes that the use of outdated methods and approaches to learning can lead to a loss of the potential and opportunities of the future generation.